GERAKAN KEAGAMAAN SEBAGAI PELOPOR TERBENTUKNYA DINASTI SAFAWI DAN KEMAJUAN PENDIDIKAN ISLAM PERSIA - Muhaimin, Rizal; Iskarim, Mochamad (UIN Antasari Banjarmasin, 2024)
The Safavid dynasty was a dynasty that experienced rapid civilizational progress in the Islamic Middle Ages. This was based on the existence of a religious movement which was a pioneer in utilizing politics for the glory of the Syafawi Dynasty. This research aims to find out what kind of religious movements were carried out during the Safavid dynasty and how education progressed during that period. This research uses a qualitative approach with the type of library research. The data collection method used is documentation. The data is then analyzed using descriptive techniques, then interpretive steps, and then conclusions are drawn. The results of the research are that the Safavid dynasty developed through the Shiite religious movement spearheaded by Safi Ad-Din. This movement was carried out by the Sufis against the rulers of the Syafawi Dynasty, causing the religious movement to turn into a political movement. The form of education and intellectual life during the Safavid Dynasty was aimed at strengthening Shiite ideological doctrine. Shiite ideology is very strong in spreading its understandings throughout all levels of society in order to strengthen power. The Syafawi dynasty made rapid progress in the fields of politics and government, the education system and the economy. The peak of the Safavid Dynasty's scientific and educational glory was realized during the time of Shah Abbas I with the establishment of 162 mosques and 48 educational centers. Keyword: Religious Movements; Safavid Dynasty; Islamic Education.